Extraction, Partial Purification and Characterisation of a Protease Extracted from Kesinai (Streblus Asper Lour.) Leaves, and its Potential Application in the Production of Cheddar Cheese - Pagthinathan, Mylvaganam (2011)
Calf-rennet is a conventional milk-clotting enzyme, which is most widely used coagulant in cheese-making all over the world. The world wide reduced supply of calf rennet and increase of cheese production have led to a systematic investigation of calf-rennet substitutes. Extracts of ‘kesinai’ (Streblus asper) leaves have been investigated as a source of enzymes to be used in cheese-making as an alternative source of calf rennet. The overall aim of this study was to evaluate the properties and application of Streblus asper leaf protease as a rennet substitute in cheese-making. A milk-clotting protease was extracted from kesinai leaves using 100 mM Tris-HCl buffer (pH 7.4) and several other buffers. Purification was carried out using acetone precipitation, and ion-exchange and size-exclusion chromatography. Results obtained showed that 100 mM Tris-HCl buffer (pH 7.4) was found to be the most effective extraction buffer. A higher yield of the kesinai protease was obtained using acetone precipitation as compared to ammonium sulphate precipitation. The ratio of cold acetone to crude extract of 1.25:1 was found to be the most suitable ratio for the partial purification of the protease. After the final purification step, the enzyme was partially purified 3.3 fold with a 42.3% of recovery. The partially purified protease was characterised and it showed an optimum activity at 60 oC and pH 7.4. The enzyme was stable up to 70 oC for one hour, and residual activities at pH 6.0 to 10.0 were 72.4% and 70.2% of the optimum activity, respectively. The enzyme was found to have a higher temperature stability at -10 oC and 4 oC. It retained more than 98% of its activity 7 days after storage at both -10 and 40C. The enzyme was inhibited by PMSF and trypsin inhibitor by 98% and 95.87% relative to the initial activity, respectively, suggesting the presence of serine residue at the active site. Ca2+ had a slight stimulating effect while, Hg2+, Zn2+ and Pb2+ had strong inhibitory effects on the enzyme activity. The partially purified enzyme appeared as a single band on SDS PAGE with an apparent molecular weight of 75.8 kDa. The maximum coagulation activity was observed at pH 6.0 and at temperature 70 oC. The presence of CaCl2 up to 10 mM increased the milk-clotting activity while addition of NaCl decreased the milk-clotting activity. The milk-coagulation was also strengthened by increase enzyme concentration Cheddar cheese was prepared using the acetone-precipitated enzyme and commercial enzyme (chymosin), and the physico-chemical, biochemical and sensory propertieswere determined throughout two months of ripening. The yield of cheese produced using the commercial enzyme was 6% higher (p<0.05) than the yield obtained with kesinai enzymes. Cheeses made from kesinai enzyme and commercial enzyme were proximate compositionally alike except for moisture, protein contents and pH. The moisture content (42.67 ± 0.47%) of cheese made with commercial enzyme was lower than the moisture (43.88 ± 0.99%) of cheese made with kesinai enzyme, while the protein content (21.02 ± 0.41%) and pH (4.79 ± 0.03) were (p<0.05) higher in cheese made with commercial enzyme than the protein content (18.87 ± 0.32%) and pH (4.72 ± 0.01) obtained from cheese made from kesinai enzyme. In both cheeses,the moisture contents declined (p<0.05) with ripening, while the pH increased with ripening time. Non protein nitrogen (NPN) (0.04 ± 0.00%) and non-casein nitrogen (NCN) (0.09 ± 0.00%), were higher (p<0.05) in the whey obtained with kesinai enzyme compared to those (NPN and NCN were 0.03 ± 0.00% and 0.06 ± 0.00%,respectively), obtained with the commercial enzyme. Protein nitrogen (PN) (2.75± 0.06%) and casein nitrogen (CN) (2.56% ± 0.05) contents of cheese made with kesinai enzyme were (p<0.05) lower than those (CN and TN were 2.93 ± 0.11% and characteristics such as hardness (811.8 ±36.6 g for cheese made from kesinai enzyme and 984.5 ± 24.2 g for cheese made from commercial enzyme), gumminess (622.8 ± 39.2 g for cheese made from kesinai enzyme and 820.9 ± 20.9 g for cheese made from commercial enzyme), and chewiness (534.7 ± 17.1 g mm for cheese made from kesinai enzyme and 735.3 ± 14.6 g mm for cheese made from commercial enzyme),increased in both types of cheese during the early stage of ripening and decrease gradually at end of ripening whereas springiness and cohesiveness showed similar changes in both cheeses during the ripened period. It is concluded that kesinai protease could be used for the production of Cheddar cheese or it can be used together with another commercial enzyme in cheese production.